Evidence for myosin light chain kinase mediating noradrenaline-evoked cation current in rabbit portal vein myocytes - Aromolaran, A S (Blackwell Science Inc, 2000)
1. The role of myosin light chain kinase (MLCK) in the activation of the noradrenaline-evoked non-selective cation current (I(cat)) was examined with the whole-cell recording technique in single rabbit portal vein smooth muscle cells. 2. Intracellular dialysis with 5 μm MLCK((11–19))amide, a substrate-specific peptide inhibitor of MLCK, markedly reduced the amplitude and rate of activation of noradrenaline-evoked I(cat). A similar result was obtained when the cells were dialysed with 10 μm AV25, which also inhibits MLCK by an action at the auto-inhibitory domain of MLCK. 3. Inhibitors of binding of ATP to MLCK, wortmannin and synthetic naphthalenesulphonyl derivatives (ML-7 and ML-9), at micromolar concentrations, also reduced the amplitude of noradrenaline-evoked I(cat). 4. ML-7 and ML-9 (both at 5 μm) reduced the amplitude of I(cat) induced by both guanosine 5′-O-(3-thiotriphosphate) (GTPγS) and 1-oleoyl-2-acetyl-sn-glycerol (OAG). 5. MLCK((11–19))amide, AV25 and ML-9 did not inhibit the noradrenaline-evoked Ca(2+)-activated potassium current at a holding potential of 0 mV. In addition, MLCK((11–19))amide and AV25 did not reduce the non-selective cation current induced by ATP in rabbit ear artery cells. 6. Intracellular dialysis with 2 μm Ca(2+) and 9 μm calmodulin activated I(cat), which developed over a period of about 5 min. 7. Intracellular dialysis with the non-hydrolysable analogue of ATP, 5′-adenylylimidodiphosphate (AMP-PNP), reduced the amplitude and rate of activation of noradrenaline-evoked I(cat). 8. The results indicate that MLCK mediates noradrenaline-activated I(cat) in rabbit portal vein smooth muscle cells.